Free and underfit-scavenger river dynamics dominate the large Amazonian Pacaya-Samiria wetland structure - Rojas, Tania V.; Abad, Jorge D.; Roque, Wendy R.; Latrubesse, Edgardo M.; Shan, Jingfu (Frontiers in Environmental Science, 2023)
The Peruvian Amazon is known for harboring the greatest biodiversity on the planet, with a world record for biodiversity per unit area. Previous studies suggested that the high ecological value depends on correlations between ecosystem functionality and river dynamics, particularly how flooding patterns, and seasonal inundation control vegetation patches. Herein, the variation and timing of water cycles influence the distribution of habitats and river morphodynamics, generating complex erosion-depositional processes that control fishing activity. This study examines the hydrogeomorphology of the Peruvian tropical wetland of Pacaya Samiria, located in Western Amazonia, and its role in the distribution of aquatic habitats. By using remote sensing techniques, the hydrogeomorphological connectivity that bounds the Pacaya Samiria National Reserve is characterized by ancient to modern processes. Additionally, river signatures developed by the Ucayali, Marañon, Huallaga, Pacaya, and Samiria Rivers overlap with fish extraction and dominant vegetation to assess how geomorphology is associated with the spatial distribution of fishing zones. Results indicated that paleochannels regulate wetland drainage within the Ucamara Depression, supporting stational water stagnation, vegetation cover, and formation of carbon and detritus-rich, relevant aspects to understand fish traits. Moreover, the Ucayali River dominates river dynamics in the Pacaya Samiria wetland, thus playing a pivotal role in shaping the complexity of streams and lakes. Furthermore, underfit-scavenger meandering rivers are observed in areas where paleochannels from large rivers are found. A geomorphological characterization of drainage patterns in freshwater environments, such as Amazonian wetlands, is crucial to develop sound management strategies. This methodological approach is expected to support decision-making in conservation actions in Amazonian environments based on understanding wetland connectivity and hydrogeomorphological behavior and their influence on commercial fisheries.